2018
DOI: 10.1038/s41380-017-0010-4
|View full text |Cite|
|
Sign up to set email alerts
|

Psychiatric genetics and the structure of psychopathology

Abstract: For over a century, psychiatric disorders have been defined by expert opinion and clinical observation. The modern DSM has relied on a consensus of experts to define categorical syndromes based on clusters of symptoms and signs, and, to some extent, external validators, such as longitudinal course and response to treatment. In the absence of an established etiology, psychiatry has struggled to validate these descriptive syndromes, and to define the boundaries between disorders and between normal and pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
244
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 333 publications
(265 citation statements)
references
References 111 publications
12
244
0
9
Order By: Relevance
“…These results of genetic continuity carry implications for molecular genetic studies of eating disorders (Boraska et al, ; Duncan et al, ; Liu, Study, Kelsoe, & Greenwood, ) They provide preliminary support for broadening phenotypes included in molecular genetic studies to encompass a wide range of eating pathology phenotypes, to increase power to detect shared susceptibility loci (Smoller et al, ) Furthermore, given substantial stable genetic influences across adolescence and young adulthood, molecular genetic studies might not benefit from stratifying developmental samples by age. Identifying specific genes or polygenic risk scores may in turn inform precision medicine, for example, by using genetic markers to predict disease risk or treatment response.…”
Section: Discussionmentioning
confidence: 98%
“…These results of genetic continuity carry implications for molecular genetic studies of eating disorders (Boraska et al, ; Duncan et al, ; Liu, Study, Kelsoe, & Greenwood, ) They provide preliminary support for broadening phenotypes included in molecular genetic studies to encompass a wide range of eating pathology phenotypes, to increase power to detect shared susceptibility loci (Smoller et al, ) Furthermore, given substantial stable genetic influences across adolescence and young adulthood, molecular genetic studies might not benefit from stratifying developmental samples by age. Identifying specific genes or polygenic risk scores may in turn inform precision medicine, for example, by using genetic markers to predict disease risk or treatment response.…”
Section: Discussionmentioning
confidence: 98%
“…In our study SZ PRS was not significantly associated with JTC. However, as PRS technique is based on contribution of common SNPs variation to genetic risk, its detection is strictly dependent on statistical power 45,46 . Although GWAS studies on schizophrenia have already identified a substantial number of genetic variants by increasing sample size 17 , SZ PRS still accounts for 7% of the variance in schizophrenia liability, as we also found in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropsychiatric disorders have substantial heritability, as shown by many studies of twins and families (1). Genomewide association studies (GWAS) have shown that common genetic variants account for some of this heritability, and that some of this heritability is shared across neuropsychiatric disorders (2)(3)(4)(5). The genetic overlap across disorders may partly explain why these disorders tend to co-occur with one another in both clinical and community samples (6).…”
Section: Introductionmentioning
confidence: 99%